2012
DOI: 10.3390/ijms13021620
|View full text |Cite
|
Sign up to set email alerts
|

Acidic Polysaccharide Extracts from Gastrodia Rhizomes Suppress the Atherosclerosis Risk Index through Inhibition of the Serum Cholesterol Composition in Sprague Dawley Rats Fed a High-Fat Diet

Abstract: Obesity is associated with a broad spectrum of cardio-metabolic disturbances, including atherosclerosis and cardiovascular disease (CDV). A high-fat diet has been shown to cause an elevation of the plasma cholesterol levels in humans, and the control of serum cholesterol has been demonstrated to be important in the prevention of CVD and atherosclerosis. The aims of this study were to demonstrate that crude and acidic polysaccharide extracts from Gastrodia rhizomes suppress atherosclerosis through the regulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…The overproduction of VLDL has been considered as an important cause for the initiation and development of atherosclerosis, and this event is highly associated with insulin signaling [10,21]. Although some polysaccharides have shown the ability to inhibit atherosclerosis, the underlying mechanism of polysaccharides against atherosclerosis is still unknown to us so far [15,16]. In the present study, we found that long-term consumption of HFD caused atherosclerosis, serum VLDL overproduction, and IR in LDLr −/− mice, suggesting HFDinduced atherosclerosis is related to VLDL overproduction by impaired insulin signaling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overproduction of VLDL has been considered as an important cause for the initiation and development of atherosclerosis, and this event is highly associated with insulin signaling [10,21]. Although some polysaccharides have shown the ability to inhibit atherosclerosis, the underlying mechanism of polysaccharides against atherosclerosis is still unknown to us so far [15,16]. In the present study, we found that long-term consumption of HFD caused atherosclerosis, serum VLDL overproduction, and IR in LDLr −/− mice, suggesting HFDinduced atherosclerosis is related to VLDL overproduction by impaired insulin signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Since the conversion of macrophages into foam cells is a major hallmark of early stage atherosclerotic lesions and LJP61A is suggested to exert the bioactivity as a whole molecule after oral administration, we guess that LJP61A might have the potential of preventing atherosclerosis development. Although some other crude polysaccharides from Gastrodia rhizomes and Ganoderma lucidum have also been shown to exhibit this function, the mechanism related to prevention of atherosclerosis by polysaccharides is still not reported so far . The main purpose of the present work is to estimate the actions of LJP61A on decreasing VLDL secretion and attenuating atherosclerosis in diet‐induced insulin‐resistant mice.…”
Section: Introductionmentioning
confidence: 97%
“…The atherogenic index (A.I.) was calculated according to the equations of Kim et al [9]. Liver lipids were extracted according to the Folch et al [10] procedure; triacylglycerols (TAG) and cholesterol concentrations were measured using enzymatic determination from BioSystems Laboratories.…”
Section: Biochemical Parametersmentioning
confidence: 99%
“…An inordinate number of bacterial EPSs has attracted the interest of many scientists who have examined their composition, structure, biosynthesis, and functional properties [ 9 ]. A number of reports have been published on the anti-atherosclerosis effect of acidic EPSs and the inhibition of total cholesterol [ 10 ]. Atherosclerosis is combined with a broad spectrum of cardio-metabolic disturbances, including diabetes, arteriosclerosis, and cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%